Oral energy supplementation improves nutritional status in hemodialysis patients with protein–energy wasting: A pilot study - Qin, Aiya; Tan, Jiaxing; Hu, Wen; Liu, Yuan; Chen, Lin; Tang, Yi; Qin, Wei (Frontiers in Pharmacology, 2022)
Background: Protein-energy wasting (PEW) is highly prevalent in hemodialysis (HD) patients, which is associated with poor quality of life, complications and increased risk of mortality. A prospective study in HD patients with 2 months of oral energy supplements (OES) supplement was performed. Methods: 37 HD patients with PEW were enrolled in this prospective cohort study. Patients in OES group (n=19) received oral energy supplementation (300 kcal) and dietary recommendations while patients in non-OES group (n=18) received only dietary recommendations. The study duration was 2 months. Nutritional status of the patients were evaluated by laboratory indexes, body composition parameters and the modified quantitative subjective global assessment (MQSGA) and Malnutrition Inflammation Score (MIS). Quality of life was evaluated by Short Form Health Survey Questionnaire (SF-36). Results: After 2 months of therapy, a significant increase of serum albumin (39.6(37.6-45.8) vs 43.4(39.1-46.7) g/L; P=0.018), hemoglobin (101.0±13.6 g/L vs 111.8±11.7 g/L; P=0.042) and dietary energy intake (29.17±3.22 kcal/kg/day vs 33.60±2.72 kcal/kg/day, P < 0.001) was observed in the comparisons of baseline in the OES group. Moreover, the OES group demonstrated significant amelioration in MQSGA (9(8-13) vs 8(7-12), P<0.001) and MIS (5(3-10) vs 3(2-8), P<0.001), physical functioning (P<0.001) and mental health (P=0.046) subsections of SF-36 compared with the baseline. No electrolyte disorder and dyslipidemia were observed in OES group. Conclusions: OES in HD patients with PEW can significantly ameliorate energy supply, nutritional status, anemia and quality of life.